2017
DOI: 10.1063/1.4980927
|View full text |Cite
|
Sign up to set email alerts
|

A cluster analysis on road traffic accidents using genetic algorithms

Abstract: The analysis of traffic road accidents is increasingly important because of the accidents cost and public road safety. The availability or large data sets makes the study of factors that affect the frequency and severity accidents are viable. However, the data are often highly unbalanced and overlapped. We deal with the data set of the road traffic accidents recorded in Christchurch, New Zealand, from 2000-2009 with a total of 26440 accidents. The data is in a binary set and there are 50 factors road traffic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Regarding k-means clustering algorithm, data mining has been used for data exploration and analysis in many fields, such as traffic safety, by using the k-means method [18,[26][27][28], which can help us better understand the complex relationship between different risk factors that contribute to unsafe traffic status. e study conducted by Sohn and Lee [15] also demonstrated that clustering based on a classification algorithm is best for road traffic status classification compared with the Bayesian neural networks and decision trees methods.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding k-means clustering algorithm, data mining has been used for data exploration and analysis in many fields, such as traffic safety, by using the k-means method [18,[26][27][28], which can help us better understand the complex relationship between different risk factors that contribute to unsafe traffic status. e study conducted by Sohn and Lee [15] also demonstrated that clustering based on a classification algorithm is best for road traffic status classification compared with the Bayesian neural networks and decision trees methods.…”
Section: Methodsmentioning
confidence: 99%
“…Te composition of a road's spatial alignment is a comprehensive product of an integrated part of an integrated transportation process. Since the 1930s, national road design standards, policy studies, and guidelines have been implemented to address economic, environmental, and other social issues [1,2]. However, more and more people are afected by man-made road disasters, making road risk control crucial [3].…”
Section: Introductionmentioning
confidence: 99%